Long-term results of ligation of intersphincteric fistula tract (LIFT) for management of anal fistula - Anaraki,Fakhrosadat (2016)
ABSTRACT Background: Ligation of intersphincteric fistula tract technique is a new sphincter saving method with good results in management of anal fistula, but few studies report long-term follow-up data. Material and methods: This study investigated the use of ligation of intersphincteric fistula tract as a sphincter saving method based on long term results. This was a retrospective review of prospectively collected data. The study was conducted at two tertiary care university medical centers. 36 patients with complex fistula from January 2010 to January 2014 treated with classic ligation of intersphincteric fistula tract were retrospectively followed. Demographic data, previous repair attempts, the type of the fistula and score of fecal continence were collected. The procedure was performed by colorectal surgeons. Primary healing rate, failures and fecal incontinence score of patients were followed for 6-48 months. Results: A total of 36 patients underwent ligation of intersphincteric fistula tract during 24 months. The mean age of the patients was 35 years and 50% had two previous attempts at surgery. A total of 25 patients (69/5%) had high transsphincteric fistula. The mean follow up was 27 months. Successful fistula closure was achieved in 63/8% of the patients (23 of 36). The mean time of recurrence was 4.5 weeks. Only one (2/77%) patient reported gas incontinence (score: 3) after the procedure. Conclusion: The recurrence rate and fecal incontinence were measured. The ligation of intersphincteric fistula is a promising sphincter-preserving procedure that is simple and safe. Our study demonstrates favorable long-term results of ligation of intersphincteric fistula tract for management of complex anal fistulas.